Penyuluhan Bahaya Formalin Serta Test Keberadaan Formalin Pada Produk Makanan dan Workshop Pembuatan Sabun Cuci Piring dari Bahan alami di Desa Banjarsari , Kecamatan Ciawi, Kabupaten Bogor - Yulis Adriana; Rahmi Fatria Fajar; Dede Komarudin; Mutawalli Sjahid Latief; Febri Hidayat; Dewi Rahma Fitri (Lembaga Publikasi Ilmiah Nusantara, 2026)
The community service program that has been implemented by the Pharmacy study program of the Al Kamal Institute of Science and Technology regarding Counseling on the Dangers of Formaldehyde and Testing for the Presence of Formaldehyde in Food Products and a Workshop on Making Dishwashing Soap from Natural Ingredients in Banjarsari Village, Ciawi District, Bogor Regency is an educational activity to the community on the dangers of formaldehyde in food products for the short term and long term effects and how the appearance of food products that are indicated to contain formaldehyde so that people avoid consuming foods that are dangerous for health. Furthermore, the implementation of a workshop on making dishwashing soap from natural ingredients, namely lime, pandan leaves and soap nuts. The purpose of this activity is to increase public knowledge about the dangers of using formaldehyde in food and the importance of food safety and empowering the community through training in making herbal dishwashing soap based on natural ingredients that are environmentally friendly and have economic value. The results of formalin testing on several food products found in Banjarsari village were found to be all negative for containing formaldehyde and the implementation of a workshop on making dishwashing soap from natural ingredients such as pandan leaves, lime and soap nuts succeeded in providing new knowledge and skills to the community in utilizing natural ingredients as safe and environmentally friendly cleaning products.